Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Wykonaj mnożnie i zredukuj wyrazy podobne. 4.63 gwiazdek na podstawie 8 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ \ (x+1)(x-1)(x^2-1)(x^3-1)=(x^2-x+x-1)(x^2-1)(x^3-1)=`

`=(x^2-1)(x^2-1)(x^3-1)=(x^4-x^2-x^2+1)(x^3-1)=(x^4-2x^2+1)(x^3-1)=`

`=(x^3-1)(x^4-2x^2+1)=x^3*x^4+x^3*(-2x^2)+x^3*1-1*x^4-1*(-2x^2)-1*1=`

`=x^7-2x^5+x^3-x^4+2x^2-1`

`b) \ \ (1-x)(1+x)(1+x^2)(1+x^4)=(1^2+x-x-x^2)(1+x^2)(1+x^4)=`

`=(1-x^2)(1+x^2)(1+x^4)=(1+x^2-x^2-x^4)(1+x^4)=(1-x^4)(1+x^4)=`

`=1+x^4-x^4-x^8=1-x^8`

`c) \ \ (a+b)(a^2-ab+b^2)(a^3-b^3)=(a^3-a^2b+ab^2+a^2b-ab^2+b^3)(a^3-b^3)=`

`=(a^3+b^3)(a^3-b^3)=(a^6-a^3b^3+b^3a^3-b^6)=(a^6-a^3b^3+a^3b^3-b^6)=a^6-b^6`

`d) \ \ (a-b)(a^2+ab+b^2)(a^3-b^3)=(a^3+a^2b+ab^2-a^2b-ab^2-b^3)(a^3-b^3)=`

`=(a^3-b^3)(a^3-b^3)=a^6-a^3b^3-a^3b^3+b^6=a^6-2a^3b^3+b^6`